Prevalence of gestational diabetes mellitus evaluated by universal screening with a 75‐g, 2‐hour oral glucose tolerance test and IADPSG criteria. Issue 2 (13th June 2017) - Karcaaltincaba, Deniz; Calis, Pinar; Ocal, Nagehan; Ozek, Aykut; Altug Inan, Melis; Bayram, Merih
Abstract: Objective: To determine the prevalence of gestational diabetes mellitus (GDM) and its association with maternal age among Turkish women diagnosed by International Association of Diabetes and Pregnancy Study Group (IADPSG) criteria. Methods: A cross‐sectional study was conducted in 2013–2015 among non‐diabetic pregnant women aged 18–49 years who were universally screened for GDM by IADPSG criteria. The percentage of women meeting each diagnostic threshold and the prevalence of GDM by age group were calculated. Linear trends were evaluated by logistic regression. Results: Among 1434 women screened, 159 (11.1%, 95% confidence interval 9.5%–12.7%) were diagnosed with GDM; eleven of these women had been diagnosed according to a fasting glucose level in the first trimester. The prevalence of GDM was 6.6% (10/151), 7.3% (37/507), 8.8% (42/479), 16.7% (45/270), and 35.2% (25/71) among women aged younger than 25, 25–29, 30–34, 35–39, and 40 years or older, respectively. GDM prevalence increased with age ( P <0.001). The numbers of women diagnosed with GDM in the second trimester who exceeded one, two, and three thresholds of the 2‐hour oral glucose tolerance test were 66 (44.6%), 52 (35.1%), and 30 (20.3%), respectively. Conclusion: Prevalence of GDM was correlated with maternal age. Most women diagnosed in the second trimester exceeded the threshold at only one of the three timepoints. Abstract : Prevalence of gestational diabetes, and thus treatment need for glucose intolerance, was higher by IADPSG criteria than by other criteria and correlated with maternal age.